INTEGRASI SISTEM TELEKOMUNIKASI IP-PABX MULTIBRAND PADA LEMBAGA PENDIDIKAN - Sukmandhani, Arief Agus; Ponco Sulistyo, Febryo Ponco Sulistyo (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2018)
Multibrand IP-PABX Telecommunication System Integration in Educational Institutions. This research was conducted to be able to integrate Multi brand IP Pabx in one of the educational institutions so that it can make all the sites in the branch owned can communicate with each other just by dialing the extension number for both users who use analog phones and users who use IP Phones. Data is taken using the direct testing methodology on IP PABX when making a call between IP PABX and QoS (Quality of Service) captured by using the Wireshark Protocol Analyzer, the results of the monitoring will be compared with the benchmark of each of the QoS parameters so that the configuration results are the best that can be applied to Multibrand IP PABX in the utilization of H323 and SIP Trunking protocols as a link between IP PABX